Comparison of craniofacial morphology, head posture and hyoid bone position with different breathing patterns - Faruk Izzet Ucar; Abdullah Ekizer; Tancan Uysal (Saudi Dental Journal)
Objectives: The aim of this study was to evaluate differences in craniofacial morphology, head posture and hyoid bone position between mouth breathing (MB) and nasal breathing (NB) patients. Methods: Mouth breathing patients comprised 34 skeletal Class I subjects with a mean age of 12.8 ± 1.5 years (range: 12.0–15.2 years). Thirty-two subjects with skeletal Class I relationship were included in the NB group (mean 13.5 ± 1.3 years; range: 12.2–14.8 years). Twenty-seven measurements (15 angular and 12 linear) were used for the craniofacial analysis. Additionally, 12 measurements were evaluated for head posture (eight measurements) and hyoid bone position (four measurements). Student’s t-test was used for the statistical analysis. Probability values <0.05 were accepted as significant. Results: Statistical comparisons showed that sagittal measurements including SNA (p < 0.01), ANB (p < 0.01), A to N perp (p < 0.05), convexity (p < 0.05), IMPA (p < 0.05) and overbite (p < 0.05) measurements were found to be lower in MB patients compared to NB. Vertical measurements including SN-MP (p < 0.01) and PP-GoGn (p < 0.01), S-N (p <0.05) and anterior facial height (p < 0.05) were significantly higher in MB patients, while the odontoid proses and palatal plane angle (OPT-PP) was greater and true vertical line and palatal plane angle (Vert-PP) was smaller in MB patients compared to NB group (p < 0.05 for both). No statistically significant differences were found regarding the hyoid bone position between both groups. Conclusions: The maxilla was more retrognathic in MB patients. Additionally, the palatal plane had a posterior rotation in MB patients. However, no significant differences were found in the hyoid bone position between MB and NB patients. Keywords: Mouth breathing, Craniofacial morphology, Hyoid bone